Writing Research Article Abstracts by Using Genre-Based Mentoring Method: Viewed from Rhetorical Moves and Tenses Usage - Dedi Jasrial; Safnil Arsyad; Arono Arono; Wisma Yunita (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Studies on the rhetorical structure and linguistic features of research article published in reputable international journals, and a genre-based approach to teaching writing have received considerable attention from scholars in the last decade. However, little research has been conducted on writing RA abstracts based on the standard of international journals by combining the genre-based approach and mentoring process. Therefore, this study intends to address such a gap by applying the genre-based mentoring method to help improve the rhetorical moves and tenses usage of RA abstract drafts written by lecturers in social and humanities in Bengkulu. The participants of this study consisted of 20 lecturers. This study used the frameworks of Swales and Feak (2009) for move structures and Swales and Feak (2012) for tenses usage. These framework were used to evaluate the RA abstract drafts of the participants. The findings confirm that the quality of RA abstract drafts showed a better improvement viewed from the frequency of the rhetorical moves and the use of appropriate tense. It indicates that the RA abstract drafts of the participant have complied with the structure of international journals in terms of rhetorical moves and the use of appropriate tenses. Moreover, genre-based mentoring is effectively used in teaching academic